Adipose-derived stem cell exosomes: emerging roles and therapeutic application - Gong, Yuhan; Ma, Hui; Zheng, Zhongren; Wang, Xinjie; Zhang, Jiahua; Zhao, Xiaowei (Frontiers in Pharmacology, 2025)
Stem cell-derived exosomes have broad application prospects in different medical fields, and are increasingly being considered a replacement for Mesenchymal stromal cells (MSCs) therapy. Adipose-derived stem cells (ADSCs) are an efficient and high-quality source of stem cell exosomes because ADSCs can be easily obtained from autologous adipose tissue and there are only minor ethical concerns, also ADSCs shown multipotent differentiation potential, self-renewal potential, low immunogenicity, and high proliferation rate. Exosomes derived from ADSCs have the function of promoting tissue regeneration through activation or inhibition of multiple signaling pathways (such as Wnt/βcatenin, PI3K/Akt), and immunomodulation, angiogenesis, cell migration, proliferation and differentiation, and tissue remodeling. This review presents the current state of knowledge on ADSCs exosomes and summarizes the use of ADSCs exosomes in stem cell-free therapies for the treatment of diabetes mellitus, cardiovascular, wound healing, neurodegenerative, skeletal, respiratory diseases, and skin aging and other conditions, thus providing novel insights into the clinical applications of MSC-derived exosomes in disease management.